Behavioural response thresholds of marine fish species for pulsed electric fields - Pim G. Boute; Pim G. Boute; Andres Hagmayer; Koen Smid; Remco P. M. Pieters; Martin J. Lankheet (Frontiers in Marine Science, 2024)
Electrical pulse trawling is an alternative to conventional beam trawling for common sole (Solea solea), with substantially less discards, lower fuel consumption, and reduced impact on the benthic ecosystem. Pulsed electric fields are used to drive the fish from the seafloor and immobilise them in front of the nets. Concerns exist, however, that the electric fields may affect fishes outside the trawl track. Here, we address these concerns by measuring amplitude thresholds for behavioural responses and by comparing these response thresholds to simulated field strengths around fishing gear. Electroreceptive small-spotted catshark (Scyliorhinus canicula) and thornback ray (Raja clavata) as well as non-electroreceptive European seabass (Dicentrarchus labrax), turbot (Scophthalmus maximus), and common sole were, one at the time, placed in a ø2.5 m circular tank with seven, individually controlled, evenly spaced electrode pairs, spanning the diameter of the tank. Behavioural responses were assessed from camera recordings for different pulse amplitudes and for different fish positions relative to the stimulating electrodes. Electrical stimulation consisted of a Pulsed Bipolar Current at 45 Hz and 0.3 ms pulse width, similar to that used in commercial gears. Computer simulations of the electric field, verified with in situ measurements, were used to determine the field strength at the location of the animal. Thresholds for different species varied between 6.0 and 9.8 V m–1, with no significant difference between electroreceptive and non-electroreceptive species. The thresholds correspond to a distance of maximally 80 cm from the electrode arrays in simulated electric fields around commercial fishing gears. These findings suggest that electrical pulses as used in pulse trawling are unlikely to elicit a behavioural response outside the nets that surround the electrode arrays.